SOScessory / Adlan Khairulfazi, Siti Nur Sakinah Ahmad Maliki … [et al.] - Khairulfazi, Adlan; Ahmad Maliki, Siti Nur Sakinah; Mohd Zain, Nur Zulaikha; Nasir, Faezul Kamil (2017)
A security device decorated with an attractive accessory, SOScessory comes not only in the form of earrings, but can also be used as a button badge according to customer's own wishes. This safety technology product can be used at our time in unsafe condition, apart from that time; it only serves as a beauty accessories tool. This tool has an application system which works to share location to the selected contacts if they want to keep track of where the users are, for example, when it comes to kidnapping. SOScessory is small in size where would-be attackers find it difficult to identify that prey have safety devices in their accessories.